PENGUATAN LINGKUNGAN HIDUP MELALUI PENGELOLAAN PEMBERSIHAN SAMPAH DAN PENANAMAN POHON DI KABUPATEN BENGKAYANG - Boyke, Silvanus; Gerion, Elisius; Salfarini, Eligia Monixa (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
The aim of this research is to see and explore the role of government and society in strengthening the environment, especially in Bengkayang Regency. It is hoped that this research can help the government and the public know what can be done to strengthen the living environment, so that the existing environment can be maintained and managed well so that it can improve the quality of life. The method used in this research is a qualitative research method by means of interviews and observations. From the results of existing research from the government, it turns out that so far, several programs have been implemented, namely from the Public Housing and Settlement Areas, Land and Environment Services of Bengkayang Regency. Programs that have been running so far include building temporary disposal sites and final processing sites for waste management by waste cleanup teams with supervision from the environmental service. Then, to raise public awareness, the department has also held outreach to the local community. Apart from that, the department is also implementing a tree planting program and creating parks to create green open spaces that can be beneficial for strengthening the environment. Keyword: Environment, Waste Management, tree planting